Self-education as a condition for the formation of professional competence of future teachers of technology - Хріненко, Т. В. (Educational Dimension, 2012)
Hrinenko T. Self-education as a condition for the formation of professional competence of future teachers of technology. In the article the value of self-education activity of teacher of technologies is certain in forming of professional competence, maintenance of concept "self-education of teacher of technologies" is analysed.